Computation of heritage values: Towards a holistic method to assess built heritage - Zammit, Nadine; Bianco, Lino (Heritage and Sustainable Development, 2022)
The objective of this paper is to put forward a holistic, less subjective, method to value built heritage. Based on 37 seminal publications issued from 1903 to date, 24 value typologies were identified, classified and incorporated in a heritage value grid developed from the Nara Grid. This grid allows for a multi-layered valorization of aesthetic, socio-cultural, economic and informational values with respect to six heritage dimensions, namely, (i) design, (ii) materiality, (iii) function, (vi) location, (v) tradition and techniques, and (vi) spirit and memory. This formed the basis of a mathematical formula, the Heritage Value Calculation, to compute the heritage value of a given building. The resulting final value is useful in the scheduling of such sites.